2023
DOI: 10.7717/peerj.14568
|View full text |Cite
|
Sign up to set email alerts
|

Plant ingredients in Thai food: a well-rounded diet for natural bioactive associated with medicinal properties

Abstract: Background Seeking cures for chronic inflammation-associated diseases and infectious diseases caused by critical human pathogens is challenging and time-consuming. Even as the research community searches for novel bioactive agents, consuming a healthy diet with functional ability might be an effective way to delay and prevent the progression of severe health conditions. Many plant ingredients in Thai food are considered medicinal, and these vegetables, herbs, and spices collectively possess multiple biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 215 publications
0
1
0
Order By: Relevance
“…In modern society, involving stress, exposure to environmental toxins, and consumption of highly processed foods, there is a growing awareness of the benefits of a diet rich in plant-based foods for the prevention and, indeed, treatment of chronic diseases. Accumulating evidence supports the role of plant constituents in promoting physiological functions beyond basic nutrition ( Buathong & Duangsrisai, 2023 ). The traditional therapeutic application of herbs and extracts has globally laid a foundation centuries ago, and the current market for plant-based functional foods, food supplements, and drugs has shown an explosive growth.…”
Section: Introductionmentioning
confidence: 99%
“…In modern society, involving stress, exposure to environmental toxins, and consumption of highly processed foods, there is a growing awareness of the benefits of a diet rich in plant-based foods for the prevention and, indeed, treatment of chronic diseases. Accumulating evidence supports the role of plant constituents in promoting physiological functions beyond basic nutrition ( Buathong & Duangsrisai, 2023 ). The traditional therapeutic application of herbs and extracts has globally laid a foundation centuries ago, and the current market for plant-based functional foods, food supplements, and drugs has shown an explosive growth.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemicals are highly regarded as excellent alternatives due to their cost-effectiveness, ready availability, ease of use, low toxicity, rapid degradability, and environmentally friendly nature [ 12 ]. The antibacterial properties of various plants have been documented, which can vary depending on factors such as plant type, composition, quantity utilized, specific microorganism targeted, pH level, and environmental temperature [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It holds a significant place in traditional medicine, where its essential oils extracted from leaves are utilized for pain-removing, wound healing, scabies treatment, ulcer management, headache, and nerve relaxation (Jing, 2014). Moreover, T. cordata has been reported to possess antimicrobial (Buathong and Duangsrisai, 2023), antidiabetic (Cajuday and Amparado, 2014), and antioxidant (Ngoitaku, 2016) properties. Studies have also suggested its capabilities to mitigate the danger of cardio-vascular disease, anti-cancers, and treating conjunctivitis (Huang et al, 2010).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%